Upaya Peningkatan Produktivitas Masyarakat Desa Kayen melalui Revitalisasi Green House Desa - Miftachul Chusna; Nurul Aini; Andrea Cahya Fantika S.; Ani Yufida Umsa (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The existence of a village greenhouse needs to be accompanied by adequate skills in its management as well as innovation in the use of plant products for the community. Therefore, this series of community service activities was carried out to gain insight into the proper management of a greenhouse in order to increase community productivity. This activity was carried out in October 2020 at the Village Green House which is located in the area of the Kayen Village Head Office, Bandarkedungmulyo District, Jombang Regency. In this activity, members of the youth organization were introduced to the management of the greenhouse and the selection of plant commodities. In addition, partners are also directed to process greenhouse plants into value-added products, namely eggplant chips and vegetable nuggets.